Garbageland: a cyberpunk tale of contemporary consumerist hyperreality (Altre Modernità, 2024)
The novel Garbageland (2001) by Cuban writer Juan Abreu stands out as a seminal work in the captivating realm of contemporary Cuban science fiction. As the first book of a trilogy, it plunges deeply into the realms of dystopia and cyberpunk, delving intricately and provocatively into the dynamics of a world consumed by hyperconsumerism and late capitalism. Set in a dystopian backdrop, the narrative unveils a society ensnared in a relentless cycle of unchecked consumption, leaving behind a wake of waste and environmental ruin. This dystopian milieu serves as a canvas for probing the social, economic, and environmental repercussions of a consumerism. This essay aims to provide an insightful overview of how the novel engages in a discourse with contemporary social theories, which identify capitalism and consumerism as existential threats to modern society.
Keywords: Dystopia; ecocriticism; contemporary Latin American science fiction; contemporary Cuban science fiction; consumer society